A STUDY TO ASSESS THE KNOWLEDGE AND ATTITUDE ON CHILD REARING PRACTICES AMONG FATHERS OF & CHILDREN OF 1-6 YEARS OF AGE, IN KASTURBA HOSPITAL, MANIPAL - A., Sreeram; A., D'Souza; E., Margaret B. (Journal of Health and Allied Sciences NU, 2013)
Objective:To assess the knowledge and attitude on child rearing practices among fathers of & children of 1-6 years of age.Materials and method:A descriptive correlational survey was done among conveniently selected 150 fathers of & children of 1-6 years of age at Kasturba Hospital, Manipal. The knowledge and attitude in childrearing practices were assessed using a demographic proforma, knowledge questionnaire and attitude scale.Result:The findings showed that fathers' had satisfactory knowledge and favourable attitude in childrearing practices. The study also revealed that there was a significant association between knowledge and type of family (p= 0.015) and that there was no significant association between attitude in childrearing practices and demographic variables.Conclusion:The study concluded that there is no relationship between knowledge and attitude on child rearing practices among fathers and fathers' had satisfactory knowledge and favourable attitude in childrearing practices.
Keywords: Knowledge; Attitude; Child rearing practices; Hospitalised children